A Comparison Of The Processing And Economics Of Uranium Recovery From Leach Slurries By Continuous Ion Exchange Or Solvent Extraction - G. M. Ritcey; M. J. Slater; B. H. Lucas (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1973)
The recovery of uranium from acid leach slurries by continuous ion exchange, or solvent extraction using sieve-plate pulse columns, is compared. Differences in processing costs are of prime concern and can be related to differences in the unit operations of the two methods, as well as the chemical and physical properties of the slurry. Parameters are defined for the operation of the solvent-in-pulp process and the design of the continuous ion exchange column. Pilot plant operating experience with both recovery systems is described, and an overall assessment of the relative costs is presented.